PENGARUH MEDIA POSTER TERHADAP CRITICAL THINKING SKILLS DI DALAM PEMBELAJARAN IPS ABAD 21 - Wafiyatu Maslahah; Lailatul Rofiah; Titin Fitria (JURNAL NALAR PENDIDIKAN, 2023)
Student of class VII at MTs Al-Khoirot don’t have critical thinking skills 21st century. The purpose of the study is to determine the effect of using poster media on students' critical thinking skills in social studies subjects for class VII at MTs Al-Khoirot and to determine the effectiveness of applying poster media to social studies subjects for class VII at MTs Al-Khoirot. Using a quantitative method of the type of Quasi Experiment. Questionnaires are used as research instruments that have been tested for validity and reliability are used as data collection in this study. Hypothesis testing with Independent t-Test, obtained a tcount greater than ttable (tcount > ttable = 2,939 > 1,697) with a significance value (sig.2-tailed) 0.006 < 0.05. So the proposed hypothesis is accepted, it is concluded that the use of poster media affects students' critical thinking skills in social studies subjects for class VII at MTs Al-Khoirot. Paired Test Sample t-Test on critical thinking skills on the distribution of 1 and 2 shows the value of Sig.(2-tailed) 0.000 <0.05 so that it can be concluded that the average critical thinking ability of students in the experimental class and control class for the distribution of the initial questionnaire and The final result has a difference, the difference in average proves that the Social Studies subject for class VII at MTs Al-Khoirot is effective in using poster media.